Quercetin-crosslinked chitosan nanoparticles: a potential treatment for allergic rhinitis - Dehong Mu; Li Zhou; Lingyu Shi; Ting Liu; Ying Guo; Hao Chen; Hongping Luo; Junhao Ma; Hui Zhang; Peizheng Xiong; Li Tian (Scientific Reports, 2024)
Abstract Allergic rhinitis (AR) remains a major health problem worldwide. Compared with traditional oral drugs, nasal administration avoids first-pass metabolism and achieve faster and more effective efficacy. In this study, we used the ion crosslinking method to prepare quercetin–chitosan nasal adaptive nanomedicine (QCS) delivery system and evaluated in the treatment of allergic rhinitis mice models. The obtained positively charged nanoparticles with a particle size of 229.2 ± 0.2 nm have excellent characteristics in encapsulation efficiency (79.604%), drug loading rate (14.068%), drug release (673.068 μg) and stability(> 7 days). Excitingly, QCS treatment significantly reduced the number of sneezing and nasal rubbing events in AR mice, while reducing the levels of inflammatory factors such as immunoglobulin E (IgE), interleukin (IL)-17, tumor necrosis factor (TNF)-α, and (IL)-6 to alleviate AR symptoms. Hematoxylin–eosin (HE) staining also showed the damaged nasal mucosa was improved. These experimental results suggest that QCS can effectively suppress allergic inflammation in a mouse model and hold promise as a therapeutic option for allergic rhinitis.